Strategic Lawsuit Against Public Participation (SLAPP) From Indonesian Law Perspective - Putri Mayessa Vegatasia Soetiyono; Yunia Estisari; Shambawa Dharma Raditya; Samaya Dharma Mandala; Anto Kustanto (APPTHI, 2025)
This study analyzes the practice of Strategic Lawsuits Against Public Participation (SLAPP) in Indonesia, highlighting national legal loopholes that enable strategic litigation to suppress public participation. The research’s novelty lies in a comprehensive evaluation of Indonesian legal provisions and the proposal of innovative legal strategies for prevention, including the integration of anti-SLAPP principles into non-sectoral procedural reforms. A normative juridical approach is combined with comparative methods, comparing anti-SLAPP practices in the United States and the United Kingdom to identify effective models of legal protection. Qualitative-descriptive data analysis, including the Bangka Belitung High Court decision Number 21/Pid/2021/PT BBL and PT KLM’s lawsuit against IPB academics, demonstrates that SLAPPs impose financial, psychological, and social burdens on activists, journalists, and civil society organizations. The strategy for preventing and handling SLAPPs must be holistic, encompassing the development of an anti-SLAPP bill, revisions to the criminal procedure code, strengthening the ITE Law and the public information disclosure law, and training judges to recognize indicators of strategic lawsuits.